Analysis of The Factors Affecting The Interest of Overseas Students In Choosing a Boarding House - Ristanti, Nila Riska; Simanjorang, Elida Florentina Sinaga; Limbong, Christine Herawati (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
A boarding house is a place to live that is needed by overseas students. In choosing a boarding house there are several factors that are taken into account by students, including price, facilities, and location. The purpose of this study is to analyze how the influence of price, facilities, and location factors influence the interest of overseas students in choosing boarding houses. This research was conducted in Kec. Southern Region, Kab. Labuhanbatu using quantitative methods. Data was collected by distributing questionnaires to 74 overseas students living in boarding houses around the South Rantau sub-district. The results showed that there was a positive influence between price, facilities, and location on the interest of overseas students in choosing boarding houses by 63% while the remaining 37% were influenced by other factors not examined by researchers.